The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1111/j.1365-2133.2004.06150.x
|View full text |Cite
|
Sign up to set email alerts
|

A case of epidermolysis bullosa acquisita with bleeding tendency due to factor VIII inhibitor (acquired haemophilia)

Abstract: 10 Zomer SF, de Wit RF, van Bronswijk JE et al. Delusions of parasitosis. A psychiatric disorder to be treated by dermatologists? An analysis of 33 patients. Br J Dermatol 1998; 138: 1030-2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…The cases of coexisting AHA and acquired bullous epidermolysis can be caused by the potential cross-reaction between type VII collagen and fVIII. 11,14 By analogy, it may be speculated that the presented case of coexisting PF and AHA may be caused by the potential crossreaction between Dsg-1 and fVIII and increased synthesis of autoantibodies against fVIII with exacerbation of AHA might have been triggered by abrupt cessation of immunosuppressive therapy (methylprednisolone) by the patient.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The cases of coexisting AHA and acquired bullous epidermolysis can be caused by the potential cross-reaction between type VII collagen and fVIII. 11,14 By analogy, it may be speculated that the presented case of coexisting PF and AHA may be caused by the potential crossreaction between Dsg-1 and fVIII and increased synthesis of autoantibodies against fVIII with exacerbation of AHA might have been triggered by abrupt cessation of immunosuppressive therapy (methylprednisolone) by the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few cases of AHA coexisting with bullous pemphigoid, mucous membrane pemphigoid, pemphigus vulgaris, linear IgA bullous dermatosis (LABD) and epidermolysis bullosa acquisita have been reported. 2,5,[10][11][12][13][14][15] Coexistence of pemphigoid and AHA is believed to be caused by homologous structural sequences between plasma fVIII and hemidesmosomal antigen BPAG2. Antibodies against plasma fVIII are likely to interact with the central collagen-like domain of BPAG2; thus, a decrease in the level of fVIII inhibitor may improve cutaneous lesions of pemphigoid.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2,19,[25][26][27][28] It is also reported that 2-8.3% of AH cases are associated with skin disorders: these include psoriasis vulgaris, bullous pemphigoid, exfoliative dermatitis, pemphigus vulgaris, erythema multiforme, erythema annulare centrifugum, scleroderma, malignant melanoma and nonspecific dermatoses. 2,6,7,19,25,26,29,30 Reported cases of autoimmune bullous dermatoses associated with AH include pemphigus vulgaris, [31][32][33] pemphigus erythematosus, 34 bullous pemphigoid, [35][36][37][38][39][40][41][42][43][44] epidermolysis bullosa acquisita [45][46][47] and anti-laminin 5 pemphigoid. 48 However, to the best of our knowledge, there have not been any previous reports of LABD associated with AH, so the present report may be the first case of LABD associated with AH.…”
Section: Discussionmentioning
confidence: 99%